Comparing transmission- and epi-BCARS: a round robin on solid-state materials - Hempel, Franz; Vernuccio, Federico; König, Lukas; Buschbeck, Robin; Rüsing, Michael; Cerullo, Giulio; Polli, Dario; Eng, Lukas M. (Applied Optics)
Broadband coherent anti-Stokes Raman scattering (BCARS) is a powerful spectroscopy method combining high signal intensity with spectral sensitivity, enabling rapid imaging of heterogeneous samples in biomedical research and, more recently, in crystalline materials. However, BCARS encounters spectral distortion due to a setup-dependent non-resonant background (NRB). This study assesses BCARS reproducibility through a round robin experiment using two distinct BCARS setups and crystalline materials with varying structural complexity, including diamond, 6H-SiC, KDP, and KTP. The analysis compares setup-specific NRB correction procedures, detected and NRB-removed spectra, and mode assignment. We determine the influence of BCARS setup parameters like pump wavelength, pulse width, and detection geometry and provide a practical guide for optimizing BCARS setups for solid-state applications.
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)

Low-noise balanced homodyne detection with superconducting nanowire single-photon detectors - Protte, Maximilian; Schapeler, Timon; Sperling, Jan; Bartley, Tim (Optica Quantum)
Superconducting nanowire single-photon detectors (SNSPDs) have been widely used to study the discrete nature of quantum states of light in the form of photon-counting experiments. We show that SNSPDs can also be used to study continuous variables of optical quantum states by performing homodyne detection at a bandwidth of 400 kHz. By measuring the interference of a continuous-wave field of a local oscillator with the field of the vacuum state using two SNSPDs, we show that the variance of the difference in count rates is linearly proportional to the photon flux of the local oscillator over almost five orders of magnitude. The resulting shot-noise clearance of (46.0 ± 1.1) dB is the highest reported clearance for a balanced optical homodyne detector, demonstrating their potential for measuring highly squeezed states in the continuous-wave regime. In addition, we measured a CMRR = 22.4 dB. From the joint click counting statistics, we also measure the phase-dependent quadrature of a weak coherent state to demonstrate our device’s functionality as a homodyne detector.

Manipulating spectral topology and exceptional points by nonlinearity in non-Hermitian polariton systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (Physical Review Research, in press)

Photochemical Reaction Enabling the Engineering of Photonic Spin−Orbit Coupling in Organic-Crystal Optical Microcavities - Liang, Qian; Ma, Xuekai; Gu, Chunling; Ren, Jiahuan; An, Cunbin; Fu, Hongbing; Schumacher, Stefan; Liao, Qing (Journal of the American Chemical Society (JACS))

Topological edge and corner states in coupled wave lattices in nonlinear polariton condensates - Schneider, Tobias; Gao, Wenlong; Zentgraf, Thomas; Schumacher, Stefan; Ma, Xuekai (Nanophotonics)

Equivalent-circuit model that quantitatively describes domain-wall conductivity in ferroelectric lithium - Zahn, Manuel; Beyreuther, Elke; Kiseleva, Iuliia; Lotfy, Ahmed Samir; McCluskey, Conor J.; Maguire, Jesi R.; Suna, Ahmet; Rüsing, Michael; Gregg, J. Marty; Eng, Lukas M. (Physical Review Applied)
Ferroelectric domain wall (DW) conductivity (DWC) can be attributed to two separate mechanisms: (a) the injection/ejection of charge carriers across the Schottky barrier formed at the (metal-)electrode-DW junction and (b) the transport of those charge carriers along the DW. Current-voltage (I-U) characteristics, recorded at variable temperatures from LiNbO3 (LNO) DWs, are clearly able to differentiate between these two contributions. Practically, they allow us to directly quantify the physical parameters relevant to the two mechanisms (a) and (b) mentioned above. These are, for example, the resistance of the DW, the saturation current, the ideality factor, and the Schottky barrier height of the electrode-DW junction. Furthermore, the activation energies needed to initiate the thermally activated electronic transport along the DWs can be extracted. In addition, we show that electronic transport along LNO DWs can be elegantly viewed and interpreted in an adapted semiconductor picture based on a double-diode, double-resistor equivalent-circuit model, the R2D2 model. Finally, our R2D2 model was checked for its universality by successfully fitting the I-U curves of not only z-cut LNO bulk DWs, but equally of z-cut thin-film LNO DWs, and of x-cut thin-film DWs as reported in literature.
Keywords: General Physics and Astronomy

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Mehrsprachigkeit in der Schule. Sprachbildung im und durch Sachunterricht.

Tailored second harmonic generation inTi-diffused PPLN waveguides usingmicro-heaters - Babai-Hemati, Jonas; vom Bruch, Felix; Herrmann, Harald; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Roadmap on electromagnetic metamaterials and metasurfaces - Cui, Tie Jun; Zhang, Shuang; Alu, Andrea; Wegener, Martin; Pendry, John; Luo, Jie; Lai, Yun; Wang, Zuojia; Lin, Xiao; Chen, Hongsheng; Chen, Ping; Wu, Rui-Xin; et al. (Journal of Physics: Photonics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

ADMM-TGV image restoration for scientific applications with unbiased parameter choice - Zietlow, Christian; Lindner, Jörg (Numerical Algorithms)

Dynamics of Electron–Hole Coulomb Attractive Energy and Dipole Moment of Hot Excitons in Donor–Acceptor Polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Decomposing large unitaries into multimode devices of arbitrary size - Arends, Christian; Wolf, Lasse Lennart; Meinecke, Jasmin; Barkhofen, Sonja; Weich, Tobias; Bartley, Tim (Physical Review Research)
Keywords: General Physics and Astronomy

Derivation of Miller's rule for the nonlinear optical susceptibility of a quantum anharmonic oscillator - Meyer, Maximilian Tim; Schindlmayr, Arno (Journal of Physics B: Atomic, Molecular and Optical Physics)
Miller's rule is an empirical relation between the nonlinear and linear optical coefficients that applies to a large class of materials but has only been rigorously derived for the classical Lorentz model with a weak anharmonic perturbation. In this work, we extend the proof and present a detailed derivation of Miller's rule for an equivalent quantum-mechanical anharmonic oscillator. For this purpose, the classical concept of velocity-dependent damping inherent to the Lorentz model is replaced by an adiabatic switch-on of the external electric field, which allows a unified treatment of the classical and quantum-mechanical systems using identical potentials and fields. Although the dynamics of the resulting charge oscillations, and hence the induced polarizations, deviate due to the finite zero-point motion in the quantum-mechanical framework, we find that Miller's rule is nevertheless identical in both cases up to terms of first order in the anharmonicity. With a view to practical applications, especially in the context of ab initio calculations for the optical response where adiabatically switched-on fields are widely assumed, we demonstrate that a correct treatment of finite broadening parameters is essential to avoid spurious errors that may falsely suggest a violation of Miller's rule, and we illustrate this point by means of a numerical example.

Scalable quantum detector tomography by high-performance computing - Schapeler, Timon; Schade, Robert; Lass, Michael; Plessl, Christian; Bartley, Tim (arXiv:2404.02844)
At large scales, quantum systems may become advantageous over their classical counterparts at performing certain tasks. Developing tools to analyse these systems at the relevant scales, in a manner consistent with quantum mechanics, is therefore critical to benchmarking performance and characterising their operation. While classical computational approaches cannot perform like-for-like computations of quantum systems beyond a certain scale, classical high-performance computing (HPC) may nevertheless be useful for precisely these characterisation and certification tasks. By developing open-source customised algorithms using high-performance computing, we perform quantum tomography on a megascale quantum photonic detector covering a Hilbert space of $10^6$. This requires finding $10^8$ elements of the matrix corresponding to the positive operator valued measure (POVM), the quantum description of the detector, and is achieved in minutes of computation time. Moreover, by exploiting the structure of the problem, we achieve highly efficient parallel scaling, paving the way for quantum objects up to a system size of $10^{12}$ elements to be reconstructed using this method. In general, this shows that a consistent quantum mechanical description of quantum phenomena is applicable at everyday scales. More concretely, this enables the reconstruction of large-scale quantum sources, processes and detectors used in computation and sampling tasks, which may be necessary to prove their nonclassical character or quantum computational advantage.

Interdisciplinary approaches between physics and art using the example of optical experiments and artistic light installations - Wolke, Nathalie; Laumann, Daniel; Webersen, Yvonne (Physics Education)

Unbreakable and breakable quantum censorship - Pinske, Julien; Sperling, Jan (Physical Review A)

Realization of high-fidelity unitary operations on up to 64 frequency bins - De, Syamsundar; Ansari, Vahid; Sperling, Jan; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Research)
The ability to apply user-chosen large-scale unitary operations with high fidelity to a quantum state is key to realizing future photonic quantum technologies. Here, we realize the implementation of programmable unitary operations on up to 64 frequency-bin modes. To benchmark the performance of our system, we probe different quantum walk unitary operations, in particular, Grover walks on four-dimensional hypercubes with similarities exceeding 95% and quantum walks with 400 steps on circles and finite lines with similarities of 98%. Our results open a path toward implementing high-quality unitary operations, which can form the basis for applications in complex tasks, such as Gaussian boson sampling. Published by the American Physical Society 2024

Evaluation of a university seminar on the use of digital media in the physics classroom - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Journal of Physics: Conference Series)
Abstract Fostering digital competencies is an important aspect of pre-service teacher education. However, for physics, there is a lack of systematically surveyed and evidence-based seminars that specifically take into account relevant research findings. Thus, we developed a research-based seminar on the effective use of digital media in physics classrooms and investigated its effects on pre-service teachers (PSTs) professional competencies in a mixed-methods design. Our quantitative analyses of different competence components surveyed in a pre-post-design indicate that the seminar leads to an increase in motivation to use digital media in the physics classroom. Nevertheless, no significant increase in digital-media PCK was found, which could be due to the small sample. The seminar design, however, was predominantly evaluated positively by experts and PSTs in guided interviews. Based on the results, it is planned to further refine the original seminar using a Design-Based Research approach.